Influence of supplemental light on sow performance during and after lactation - Stevenson, Jeffrey S.; Pollmann, D.S.; Davis, Duane L.; Murphy, James P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A study involving 327 crossbred sows was conducted to determine whether providing supplemental light in farrowing rooms would influence litter weight, number of pigs weaned, piglet survival rate, and subsequent rebreeding performance of sows exposed to 16 hr supplemental light/day during lactation. Litter weight was increased 7.7 lbs or .85 lb per pig weaned. More sows exposed to 16 hr light (83%) were mated by 5 days after weaning than were control sows (68%).
Keywords: Swine; Supplemental light; Sow performance; Lactation